The microfilm system for technical documentation - Rodić, Milorad; Banjac, Dragan (Journal of Production Engineering, 1984)
In modern information systems is emphasized the need for development appropriate subsystems. Because of that in the paper is explained for the needs of the technical documentations, microfilm system for creating, memorizing, keeping and processing technical informations.